2004
DOI: 10.1017/s0952836903004643
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature and above‐ground patterns during hibernation in European hamsters (Cricetus cricetus L.)

Abstract: The purpose of this study was to determine whether hibernating European hamsters Cricetus cricetus, L., 1758 stay in their burrows all winter or if they occasionally spent time above ground. If 'time (spent) above ground' (TAG) occurred regularly throughout hibernation, the second objective of this work was to categorize and quantify the patterns of TAG during winter. For this purpose, 11 European hamsters were individually housed in wire mesh cages that were buried in the ground of an outdoor enclosure. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…Surprisingly, females in 2006 had a shorter postbreeding period and consequently a shorter active season. During the postbreeding period, females have to build up body fat reserves and food stores to survive over winter (Wassmer 2004;Weinhold and Kayser 2006;Franceschini-Zink and Millesi 2008). Common hamsters can use both strategies, allowing a more flexible preparation for hibernation and a less strict annual schedule compared to non-caching hibernators (Millesi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, females in 2006 had a shorter postbreeding period and consequently a shorter active season. During the postbreeding period, females have to build up body fat reserves and food stores to survive over winter (Wassmer 2004;Weinhold and Kayser 2006;Franceschini-Zink and Millesi 2008). Common hamsters can use both strategies, allowing a more flexible preparation for hibernation and a less strict annual schedule compared to non-caching hibernators (Millesi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hamsters may not be an ideal model for hibernation, since they are not obligate hibernators and may only spend about half of their time during the hibernation season actually in torpor (i.e. Ueda and Ibuka, 1995;Wassmer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated a high individual variation in hibernation patterns under semi-natural and laboratory conditions (Wassmer 2004; Wassmer and Wollnik 1997; Wollnik and Schmidt 1995). In some individuals, T b patterns during winter resembled those of obligate hibernators.…”
Section: Introductionmentioning
confidence: 98%